Establishment of Cre/LoxP-mediated multifunctional reporter knock-in rats with the CRISPR system. - Katsuyuki Nakamura; Sara Ito; Yoshihiro Ohguchi; Toshie Jimbo; Yusaku Wada; Ryota Nakajima; Masanobu Kanou; Kei Yamana; Hiroshi Ueda (PLoS ONE)
Rats and mice are essential experimental animals in preclinical research, serving as models for various human diseases and contributing significantly to drug development. Rats offer distinct advantages over mice due to their larger size, which allows for more complex surgical procedures, repeated blood sampling, or sophisticated behavioral analysis. However, unlike the case with mice, genetically modified rat lines for achieving complex experimental objectives-such as tissue-specific gene knockout or visualization of specific cell populations-are still limited. We here established LoxP-mediated multifunctional reporter KI rats, enabling us to evaluate fluorescence, bioluminescence, and cell-killing assays simultaneously with only one gene-modified rat line. CRISPR/Cas12a, also known as CRISPR/Cpf1, was successfully used to insert the Cre sequence into a target locus to generate Cre driver rats. These results will contribute to the application of gene-modified rats for a more comprehensive understanding of physiology, and for extrapolation of their capabilities in preclinical research.